Education research in Australia: where is it conducted? - Bobis, J.; Shore, S.; Bennett, Dawn; Bennett, S.; Harrison, N.; Seddon, T. (Australian Association for Research in Education, 2013)
Research assessment exercises aim to identify research quantity and quality and provide insights into research capacity building strategies for the future. Yet with limited knowledge of the ecology of Australian educational research, there is little chance of understanding what research audits might contribute towards a capacity building agenda for such a complex field. This paper draws on secondary data analysis of research outputs submitted by 13 Australian higher education institutions to the Excellence in Research for Australia (ERA) 2010 and 2012 national research assessment exercises, to show where Australian educational research is conducted. Findings offer a profile of education researchers by location in academic organisational units within universities. By analyzing data not accessible through reported ERA data we were also able to present information about appointment profiles, specifically levels and type of appointment within universities, as well as data on institutional and geographic region, and patterns associated with type of outputs (books, book chapters, journal articles, conference papers and other outputs) and field of research. Analysis of the data reveals definitive shifts in the nature of the published outputs and in employment profiles of researchers and their location across university and regional groupings. Research audits are administrative processes that reshape institutional and disciplinary governance structures, policies, individual outputs, work practices and careers, but they are not the sum total of the field per se.